2013
DOI: 10.1002/mnfr.201300182
|View full text |Cite
|
Sign up to set email alerts
|

PBMCs reflect the immune component of the WAT transcriptome—Implications as biomarkers of metabolic health in the postprandial state

Abstract: The PBMC transcriptome may therefore provide a unique insight into the inflammatory component of metabolic health, as opposed to directly reflecting the metabolic component of the adipose tissue transcriptome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…Therefore, a different sensitivity to GSPE between adipocytes and PBMCs cannot be ruled out. These results suggest that PBMCs do not completely reflect the elements of lipid metabolism in the adipose tissue, in agreement with the results obtained by O'Grada et al (2013), who showed no correlations in the expressions of lipid-and cholesterol-related genes, such as PPARa, PPARc and ABCG1, between PBMCs and the subcutaneous adipose tissue of subjects submitted to oral lipid and glucose tolerance tests.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, a different sensitivity to GSPE between adipocytes and PBMCs cannot be ruled out. These results suggest that PBMCs do not completely reflect the elements of lipid metabolism in the adipose tissue, in agreement with the results obtained by O'Grada et al (2013), who showed no correlations in the expressions of lipid-and cholesterol-related genes, such as PPARa, PPARc and ABCG1, between PBMCs and the subcutaneous adipose tissue of subjects submitted to oral lipid and glucose tolerance tests.…”
Section: Discussionsupporting
confidence: 91%
“…Afman et al 2014). Furthermore, it has been shown that PBMCs can act as biomarkers of the metabolic adaptations that occur in different tissues such as adipose tissue, liver and muscle (Caimari et al 2010a;Rudkowska et al 2011;Oliver et al 2013;O'Grada et al 2013;Konieczna et al 2014), although there are some controversial results about this issue (Rudkowska et al 2011;O'Grada et al 2013;Afman et al 2014). In addition, other studies have demonstrated that PBMCs can reflect gene expression signatures that are characteristic of different diseases linked to a sedentary lifestyle and increased food intake, such as atherosclerosis (Kang et al 2006), chronic heart failure (Cappuzzello et al 2009) and metabolic syndrome (D'Amore et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…7,15,[22][23][24][54][55][56][57] Tissue-specific transcriptomic information requires invasive procedures, and whether changes in PBMCs are indicative of the metabolism in other tissues, although suggestive, needs confirmation. Inferring the routes of interacting biological macromolecules may be considered as a promising and complementary tool for capturing the metabolic complexity of phytochemical exposure.…”
Section: Overall Discussionmentioning
confidence: 99%
“…The postprandial response to an oral lipid tolerance test (OLTT) is a better metabolic challenge to emulate nutrient overload, in comparison to an oral glucose tolerance test (OGTT) . To study the impact of nutritional challenge on metabolism and inflammation, peripheral blood mononuclear cells (PBMC) transcriptome profiling has proved meaningful . Previously our group identified differential transcriptomic responses in inflammation‐related pathways following acute glucose or lipid challenges in the PBMC transcriptome of healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…Previously our group identified differential transcriptomic responses in inflammation‐related pathways following acute glucose or lipid challenges in the PBMC transcriptome of healthy adults. An OLTT modulated inflammatory transcriptomic biomarkers in an age and BMI‐dependent fashion, much more than an OGTT, which is often the standard metabolic challenge, to assess T2D risk . To date, the impact of gender as a potential determinant in the transcriptomic response to a metabolic challenge is unknown, despite the fact that men and women differ greatly with respect to dietary intakes and metabolic responses (relating to lipid and/or glucose metabolism) …”
Section: Introductionmentioning
confidence: 99%